(untitled) (Journal of Science and Technology, 2025)
Information serves as the cornerstone of all human pursuits and no individual can thrive without it. It is the 5th factor of production after land, labour, capital and entrepreneur, as technology advances, the volume of information at our disposal is increasing at an unprecedented rate. The study examines awareness, perception, and compliance as determinants of information security among library and information science undergraduates in universities in Kwara State. Descriptive survey research design was used. The population of the study comprises LIS undergraduates of the University of Ilorin, Kwara State University, and Al-Hikmah University. Therefore, the population for this study is 2157 students from the three (3) selected universities. The purposive sampling technique was adopted because Library and Information Science undergraduates are the target, and they serve the purpose for the study. The study used the Rao-soft calculator to get the sample size of 327. Descriptive statistics of simple percentage and frequency count were used as the method of data analysis owing to its simplicity and ease of understanding. The study found out there is a high level of awareness of information security among undergraduates in Library and Information Science in universities in Kwara State. This study also found out that undergraduates in Library and Information Science have positive perceptions towards information security. This study also found out that undergraduates in Library and Information Science strongly comply with information security practices. This study also found that difficulties with backing up, unstable power supply, insufficient storage capacity, and difficulties in navigating through devices are the challenges associated with the use of information security. The study concludes that library and information science students in universities in Kwara State have positive knowledge regarding awareness, perception, and compliance on information security. The study recommends that there should be continuous awareness campaigns among LIS undergraduates’ to maintain the high level of awareness.